Campus Criminal Victimization among Higher Education Students: A Diagnosis of Local Security in Porto - Sani, Ana (2019)
This study addressed and characterized direct and indirect criminal victimization among college students and examined the associations between victimization and other variables. The participants were 775 students of both genders with a mean age of 21.76 years. Data were collected through self-reports using the “Diagnosis of Local Security Questionnaire”. Overall, 8.6% of the students reported direct victimization, and 39.7% reported indirect victimization. The most reported crimes were robbery and theft, while the least prevalent were sexual offense, domestic violence, and fraud. Most incidents involved a stranger and occurred at night in the street. Direct victimization was associated with gender, age, marital status, student level, attendance status, and institution domain. There were significant associations between indirect victimization and nationality, student type, attendance status, and institution domain. The perception of (in)security was significantly associated with victimization. Therefore, physical and social measures are necessary to reduce crime and increase security.